Implementing practical argumentation framework as an analytic/evaluative tool in research Articles: The role of critical discourse analysis in language education - Karim Sadeghi; Javad Belali (Social Sciences and Humanities Open, 2025)
The Implications Section (IS) of research articles serves as a vital means for conveying the significance of findings to readers. This study employs the practical argumentation framework to analyze the IS of three research articles focusing on self-regulated learning. Self-regulated learning encompasses learners' ability to set goals, monitor their progress, and reflect on their learning strategies and outcomes, fostering autonomy and effective educational practices. By examining these sections, this study aims to uncover how ideological assumptions are embedded in practical arguments and the ways they influence educational policies and practices. The findings suggest that the promotion of competence, motivation, and autonomy may be subtly intertwined with regulatory discourses that could influence the autonomy of educators and learners. This research sheds light on the intersection of language, power, and ideology in academic discourse, offering valuable insights for educators, policymakers, and researchers in language education contexts.